Determinan Minat Mahasiswa Akuntansi Untuk Berkarier Menjadi Akuntan Publik - Bisma; Acynthia Ayu Wilasittha (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2024)
This research aims to demonstrate the influence of internship experience, work environment, job market considerations, and motivation on the interest of accounting students from UPN